Torn Apart? The Impact of Manufacturing Employment Decline on Black and White Americans - Eric D. Gould (Institute of Labor Economics (IZA), 2018)
This paper examines the impact of manufacturing employment decline on the socio-economic outcomes within and between black and white Americans from 1960 to 2010. Exploiting variation across cities and over time, the analysis shows that manufacturing decline negatively impacted blacks (men, women, and children) in terms of their wages, employment, marriage rates, house values, poverty rates, death rates, single parenthood, teen motherhood, child poverty, and child mortality. In addition, the decline in manufacturing increased inequality within the black community in terms of overall wages and the gaps between education groups in wages, employment, and marriage rates. Many of the same patterns are found for whites, but to a lesser degree – leading to larger gaps between whites and blacks in wages, marriage patterns, poverty, single-parenthood, and death rates. The results are robust to the inclusion or exclusion of several control variables, and the use of a "shift-share" instrument for the local manufacturing employment share. Overall, the decline in manufacturing is reducing socio-economic conditions in general while increasing inequality within and between racial groups – which is consistent with a stronger general equilibrium effect of the loss of highly-paid, lower-skilled jobs on the less-educated segments of the population.
Keywords: J10; 330; racial gaps; manufacturing decline